Psychiatric symptoms in migraine patients and their attitudes towards psychological support on stigmatization - Korkmaz, Sevda; Kazgan, Asli; Korucu, Tuba; Gonen, Murat; Yilmaz, M. Zulfu; Atmaca, Murad (Elsevier Sci Ltd, 2019)
Objective: Although migraine patients experience more psychological problems when compared to the general population, they are usually not treated. The reasons for non-treatment of these problems are not clear. The anxiety and concern of migraine patients about stigmatization may also prevent them to express psychological symptoms. The present study aimed to investigate the attitudes and behavior of migraine patients about receiving psychological help and their concerns about stigmatization. Material and method: The study group included 50 18-49 years old patients diagnosed with migraine in the neurology clinic and the control group included 50 healthy individuals with similar age, gender socio demographic characteristics with the study group. Attitude Scale Towards Seeking Professional Help (ASPH-SF), Self-Stigma in Seeking Professional Help Scale (SSPHS), Intentions to Seek Psychological Help Scale (ISHP), Stigma Scale for Receiving Psychological Help (SSRPH) and Symptom Checklist (SCL-90-R) were applied to all participants. Findings: The comparison of the patient and control groups based on SCL-90-R findings demonstrated that the patient group scores in somatization, anxiety (p = 0.000), depression (p = 0.003), anger (p = 0.02), interpersonal sensitivity (p = 0.006), phobia (p = 0.001), paranoid thoughts (p = 0.012), psychosis (p = 0.031) subscales and additional subscale (p = 0.014) and general symptom index (p = 0.001) scores were higher. Based on SCL 90, it was found that patients with higher levels of symptoms had higher social stigma scores when compared to patients with lower symptom levels (p = 0.007). Migraine patients with high symptom levels were found to have significantly lower rates of seeking psychiatric help (14% vs 33%) when compared to the control group. There was no difference between the patient and control groups based on ASPH-SF, SSPHS, ISPH and SSRPH scale scores. Conclusion: Although migraine patients exhibit higher levels of psychiatric symptoms when compared to healthy individuals, it was determined that only a minority of these patients receive psychiatric treatment. Especially patients with high level of psychiatric symptoms could have sought less psychiatric help due to the concerns of stigmatization. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Stigmatization; Migraine; Seeking psychological help